Hybrid α-Discounting and Nonstandard Neutrosophic Complex MoBiNad Framework for Digital Media Art Design in Virtual and Augmented Reality Technology - Qiuling Wang; Siyuan Fang (Neutrosophic Sets and Systems)
In this paper, we introduce a news operation on Neutrosophic Fuzzy Matrices (NFMs), which satisfies properties are absorption, commutative, and associative. The aim of this study is to research these operations in the environment of image processing, particularly for color blending into images. By using the mathematical properties of NFMs, the proposed operation helps strong and accurate processing of complex color transitions, these developments emphasize the possible of NFMs in solving recent image processing problems with effective manner. Color blending is one of the most commonly used tools today, developed using uncertainty operators in NFMs.